URGENSI METAKOGNISI DALAM PENCAPAIAN HASIL BELAJAR KIMIA DI SMA - Ramli Abdullah (Lantanida Journal, 2017)
The instructional strategy applied in learning and appropriate subject matter of Chemistry taught will be able to provide convenience for students in understanding the subject matter of Chemistry, so that learning experience will be more meaningful for students. One of the existing learning strategies is metacognition which is the students' knowledge related to their weaknesses and strengths in learning and self-regulation during learning activities such as planning, process arrangement, evaluation, commitment, minimization, procedure and conditioning. Students who have various dimensions of high metacognition will try to learn various ways to make it easy for them that learning activities are easy and fun to achieve high learning results. Thus, there is a correlation between the metacognition of students in learning with efforts to improve student learning outcomes in Chemistry subjects. The increasing of appliying various dimensions of students metacognition in learning will have an impact on improving student learning outcomes in Chemistry subjects. In the fact, the student who use / apply their metacogical dimensions in learning Chemistry subjects, students will be happy, eager and easy in learning Chemistry subjects, able to assess and predict their ability in learning Chemistry subjects process that ultimately students can achieve high learning outcomes in Chemistry subjects.